Perspectives of push-pull-mooring effects on a desire for switching to alternative crops among tobacco farmers in Thailand: A qualitative study - Phetphum, Chakkraphan; Wangwonsin, Artittaya; Prajongjeep, Atchara; Simsin, Saksin (Tobacco induced diseases, 2024)
Tobacco use contributes significantly to premature deaths worldwide. A key strategy to curb tobacco consumption involves limiting the tobacco supply through the transition to substitute crops. This study aims to provide insight into why tobacco farmers desire to switch to alternative crops and the support required for a successful transition. Semi-structured interviews were conducted with 34 tobacco farmers expressing a desire to transition to other crops in two communities in Thailand. Data were recorded and transcribed verbatim in Thai and subsequently translated into English. A deductive content analysis applied the Push-Pull-Mooring (PPM) framework, contextualizing factors for the transition among tobacco farmers. Four main categories emerged: 1) push factors, encompassing negative experiences in growing tobacco, such as poverty, health problems, and hopelessness; 2) pull factors, representing positive experiences in transitioning to alternative crops, particularly having a role model; and 3) mooring factors, highlighting characteristic disadvantages of tobacco farmers, particularly the receipt of small tobacco growing quotas. The fourth category focused on the support needed for a successful transition, including the suspension of tobacco debt payments, access to low-interest loans, and the development of marketing capabilities. The study provides a comprehensive understanding of farmers' motivations to switch from tobacco to alternative crops and outlines the necessary support for a successful transition. Offering financial assistance and enhancing the production and marketing capabilities of alternative crops are essential steps toward facilitating a successful switch for farmers and ensuring a secure livelihood beyond tobacco farming.